2022
DOI: 10.3390/jpm12020155
|View full text |Cite
|
Sign up to set email alerts
|

Areas of Interest and Social Consideration of Antidepressants on English Tweets: A Natural Language Processing Classification Study

Abstract: Background: Antidepressants are the foundation of the treatment of major depressive disorders. Despite the scientific evidence, there is still a sustained debate and concern about the efficacy of antidepressants, with widely differing opinions among the population about their positive and negative effects, which may condition people’s attitudes towards such treatments. Our aim is to investigate Twitter posts about antidepressants in order to have a better understanding of the social consideration of antidepres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 72 publications
0
13
1
Order By: Relevance
“…When discussing this study in the context of previous research on mental health topics on Twitter, it is noted that the total amount of retrieved publications for ECT is lower than the amount of retrieved tweets in other studies related to other treatments for mental disorders including antipsychotics, antidepressants, and medications for attention-deficit/hyperactivity disorder [ 27 , 28 , 34 ]. They are even lower in amount than tweets for nonpsychiatric disorders, such as statins, medications for obesity, chemotherapy agents, or antibiotics [ 24 , 34 36 ]. Such differences seem coherent with the lower prevalence of ECT use as compared to those other treatments.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…When discussing this study in the context of previous research on mental health topics on Twitter, it is noted that the total amount of retrieved publications for ECT is lower than the amount of retrieved tweets in other studies related to other treatments for mental disorders including antipsychotics, antidepressants, and medications for attention-deficit/hyperactivity disorder [ 27 , 28 , 34 ]. They are even lower in amount than tweets for nonpsychiatric disorders, such as statins, medications for obesity, chemotherapy agents, or antibiotics [ 24 , 34 36 ]. Such differences seem coherent with the lower prevalence of ECT use as compared to those other treatments.…”
Section: Discussionmentioning
confidence: 96%
“…The aforementioned previous Twitter research related to psychopharmacological drugs also described the types of users involved in discussions related to such treatments [ 28 , 34 ]. For antidepressants and antipsychotics, people with lived experience and their relatives were authors of more than half the tweets, which contrasts with the lower relative proportions of tweets from such users in ECT tweets in our study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…37 The accessibility and global presence make it a notable social media platform for healthcare providers to exert influence on the general public through tweets, as well as for scientific researchers to extract opinions from a certain population. 28 , 29 , 38 A previous study on general attitudes to antidepressants on Twitter found a low proportion of healthcare providers' referring to and discussing this. 29 However, studies specifically exploring and reporting on healthcare providers' engagement are absent.…”
Section: Introductionmentioning
confidence: 99%
“… 18 , 19 , 20 , 24 , 25 , 26 , 27 Additionally, avoiding the tension of a face-to-face consultation with a physician wearing a white coat, an informal online setting may encourage the public to explore and express their feelings more genuinely and objectively. 28 , 29 Overall, considering the emergence of mobile internet and that social media users account for nearly 60 % of the global population, social media has become a prominent source of public voices and communication. 26 , 30…”
Section: Introductionmentioning
confidence: 99%